Hepatic and Immuno-Remediating Potential of Phenolic Rich Concentrate of Phyllantus Amarus (Schum & Thonn) Whole Plant in Acute High Salt Diet Assaulted Animal Model. - Israel, Fasan Tope; Olorunnisola, Olubukola Sinbad; Adetutu, Adewale; Ajilore, Bamidele Stephen (International Journal of Scientific Research in Biological Sciences, 2021)
Gluttonous habits on high salt diets have been accounted to be deleterious to human ecosystem worldwide, derailing homeostatic threshold, immunological inertia and eventually resulting to hepatic degradation. These influences had prompted many enthusiastic researchers to further investigate on the better/alternative medicinal option to ameliorate the high preponderance of salty-diet related immunological and hepatic derangement, and subsequently complementing the non-readily available but expensive orthodox medicine. Hence, this study thus evaluated the lethal dose and protective potential of Phenolic rich concentrate (PRC) of Phyllanthus amarus (Schum and Thonn) whole plant against acute High salt diet (HSD) (8%) assaulted immunological inflammations and hepatic functionality in animal model. The healthy adult male Sprague-Dawley rats n=30 were divided into five groups: Group 1: control, Group 2: High salt diet, Group 3: High salt diet+75mg/kg/bdw, Group 4: High salt diet+100mg/kg/bdw, and Group 5: High salt diet+150mg/kg/bdw of PRC. The results obtained (p<0.05) indicated the lethal dose of the concentrate was more than 5000mg/kg/bdw. Moreover, significant excitations were recorded in the level of inflammatory cytokines, interleukin 2(IL-2), interleukin 6(IL-6), interleukin 8(IL-8), Tumor necrosis factor-alpha(TNF?) and serum enzymes, Aspartate transaminase(AST), Alkaline phosphatase(ALP), Lactate dehydrogenase(LDH) and Creatine kinase(CK) of rats fed HSD. Though IL-8 was utterly impaired among others, however, the PRC significantly ameliorated all the compromised markers to near normal level in a dose-dependent manner. The results thus established the connectivity of the plant as used in trado-medicine and also accomplished the efficacy of PRC in remediating HSD induced immunological and hepatic derangements.